Effects of isolated, confined and extreme environments on parameters of the immune system - a systematic review - Klos, Bea; Kaul, Alina; Straube, Emily; Steinhauser, Verena; Gödel, Celina; Schäfer, Franziska; Lambert, Claude; Enck, Paul; Mack, Isabelle (Frontiers in Immunology, 2025)
BackgroundThe immune system is a crucial part of the body’s defense against infection and disease. However, individuals in antigen-limited environments face unique challenges that can weaken their immune systems. This systematic review aimed to investigate the impact of an exposure to an isolated, confined and extreme (ICE) environment with limited antigen diversity on human immune parameters.MethodsA systematic literature search was conducted using PubMed, Web of Science and Cochrane Library to identify relevant studies on immune system parameters in ICE environments. The studies were grouped by ICE type (space missions, microgravity simulations like bed rest studies, space simulation units like MARS500, and Antarctic research stations) to allow for clearer comparison and analysis of immune outcomes.ResultsAnalysis of 140 studies revealed considerable heterogeneity in study designs and outcomes, reflecting the complexity of immune responses across ICE environments. Nevertheless, immune dysregulation was consistently observed across environments. Space missions and Antarctic stations, in particular, showed pronounced immune changes, likely due to low antigen diversity and extreme conditions, with higher rates of infections and allergic responses suggesting increased vulnerability. Space simulation units exhibited immune changes similar to those in actual space missions, while gravity simulation studies, which focus on fluid shifts and bone loss, showed fewer immune alterations. Across environments, most immunological measures returned to baseline after isolation, indicating resilience and the potential for recovery upon re-exposure to diverse antigens.ConclusionReduced antigen diversity in ICE environments disrupts immune function, with effects often compounded by extreme conditions. Although immune resilience and recovery post-isolation are promising, the heterogeneity in current studies highlights the need for targeted research to identify specific immune vulnerabilities and to develop countermeasures. Such measures could reduce immune-related health risks for individuals in isolated settings, including astronauts, polar researchers, and vulnerable populations on Earth, such as the elderly or immunocompromised, thereby enhancing resilience in confined environments.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023476132.